Innovative Governance Pemanfaatan Lahan Eks Tambang Bauksit PT Antam Kijang Sebagai Pusat Industri Maritim Bintan - Alfiandri, Alfiandri; Nazaki, Nazaki; Harmain, Irfan; Fattah Kaloko, Ilhamda; Riyadi, Sayed Fauzan (Jayapangus Press, 2026)
This study is motivated by the urgent need to restore and reutilize PT Antam’s former bauxite mining land in Kijang, which faces a high risk of abandonment after extraction, through innovative governance that integrates the state, state-owned enterprises, local government, universities, the private sector, and local communities. The study aims to analyze the underlying governance logic and to formulate a roadmap for land utilization that is productive, inclusive, and sustainable. A qualitative design with a grounded theory approach was employed: data were collected through in-depth interviews and document review; analysis was supported by NVivo, including open, axial, and selective coding, word-cloud exploration, and node mapping to extract categories, causal relations, strategies, and consequences. The findings reveal three main clusters—(1) institutional governance, (2) economic transformation, and (3) participatory social dimensions—with the core category of “innovative governance of post-mining state assets.” Key drivers include investment, institutional capacity, and the role of universities as knowledge producers, while major constraints involve weak inter-agency coordination, land-tenure uncertainty, regulatory gaps, and low social trust. These barriers indicate that governance success is not merely a technical matter but also an institutional and social challenge. The study concludes that effective implementation requires an adaptive polycentric network, legal certainty, public–private partnership schemes (PPP/BOT/JV), asset digitalization and ESG-oriented governance, and cross-agency performance indicators (KPIs). Consistent implementation may transform Kijang into a blue-economy maritime hub and a national model for sustainable post-mining management.